CONFLICTING COMMUNICATION STRATEGIES OF ELECTION DEBATES IN SPANISH AND UKRAINIAN POLITICAL DISCOURSE - Floyd, Laura (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article analyzes the conflicting communication strategies of the participants of the election debates in Spain in 2019. The peculiarities of communicative interaction of Spanish politicians in the conditions of political agitation on the eve of the parliamentary elections are considered the main strategies of their interaction are singled out. The purpose of the analysis was to identify and characterize the main communication strategies used by Spanish politicians during the 2019 election campaign during a televised debate. The material of the study was a card index of text fragments of speeches by Spanish politicians A. Lastro, C. Alvarez, I. Monteros, G. Rufian, A. Esteban, and others. A total of 350 micro texts were analyzed, which allowed us to identify communicative conflict as the main type of interaction in the pre-election discourse. The article defines that communicative strategy in political discourse is a general direction of interaction of politicians, which directs language means in order to realize the intention – to influence the addressee. In the pre-election discourse of political debates, the main strategies are focused on conflict interaction, within which strategies of discrediting and manipulation are singled out. The strategy of discrediting involves reducing the communicative status of the opponent and is represented by tactics of accusation and insults. The main linguistic means of implementing the strategy of discrediting are stylistically reduced vocabulary and grammatical forms of dialogic nature. The strategy of manipulation is implemented through the tactics of interpretation, declaration and intimidation. At the linguistic level, manipulation involves the use of abstract vocabulary, precedent phenomena and expressive and evaluative means. ___________ REFERENCES Bjelova, A. D. «Komunikatyvni strategii’ i taktyky: problemy systematyky.» Movni i konceptual’ni kartyny svitu10 (2004): 11–16. Grays, G. P. «Logika i rechevoe obshchenie.» Novoe v zarubezhnoy lingvistike16 (1985): 217–238. Deyk van T. Poznanie. Kommunikatsiya (Moskva, Progress, 1989). Issers, O. S. Kommunikativnye strategii i taktiki russkoy rechi (Moskva, Izdatel’stvo LKI, 2008), 288. Mikhaleva, O. L. Politicheskiy diskurs: Spetsifika manipulyativnogo vozdeystviya (Moskva, LIBROKOM, 2009), 256. Parshina, O. N. Rossiyskaya politicheskaya rech’: teoriya i praktika (Moskva, Izdatel’stvo LKI, 2007), 232. Slavova, L. L. Movna osobystist’ lidera u dzerkali politychnoi’ lingvopersonalogii’: SShA – Ukrai’na (Zhytomyr, Vyd-vo ZhDU im. I. Franka, 2012), 360. Slukhay, N. V. Suggestiya i kommunikatsiya: lingvisticheskoe programmirovanie povedeniya cheloveka (Kiev, Izdatel’sko-poligraficheskiy tsentr «Kitevskiy universiet, 2012), 319. Kondratenko, N. , Kiselova,A., Zavalska, L. «Strategies and Tactics of Communication in Parliamentary Discourse.»Studies about Languages 36 (2020): 17–29. Zheltukhina, M. R., Busygina, M. V., Merkulova, M. G., Zyubina, I. A., Buzinova, L. M. «Linguopragmatic aspect of modern communication: main political media speech strategies and tactics in the USA and the UK.» XLinguae. European Scientific Language Journal11 (2) (April 2018): 639–654.